2008
DOI: 10.1159/000155644
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Dermoscopy in Acute Diffuse and Total Alopecia of the Female Scalp: Review of Twenty Cases

Abstract: Background: Acute diffuse and total alopecia of the female scalp (ADTAFS) is a new subtype of alopecia areata that is characterized by rapid progression of diffuse alopecia of the female scalp, marked female predominance and a favorable prognosis. Differential diagnosis of other types of diffuse alopecia such as female pattern hair loss (FPHL) is necessary in some cases. Objective: To describe dermoscopic findings of ADTAFS and to investigate the possibility of utilizing dermoscopy as a diagnostic tool for ADT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
2
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(58 citation statements)
references
References 25 publications
(22 reference statements)
3
50
2
3
Order By: Relevance
“…4,5,9 Exclamation point hairs can also be spindle-like, similar to those found in cases of beaded hair (monilethrix).…”
Section: ©2011 By Anais Brasileiros De Dermatologiasupporting
confidence: 58%
See 3 more Smart Citations
“…4,5,9 Exclamation point hairs can also be spindle-like, similar to those found in cases of beaded hair (monilethrix).…”
Section: ©2011 By Anais Brasileiros De Dermatologiasupporting
confidence: 58%
“…2 Inui et al and Tosti et al were the first to publish papers on AA dermoscopic findings. 4,[7][8][9] Dermoscopy reveals the following in the initial phase of AA:…”
Section: ©2011 By Anais Brasileiros De Dermatologiamentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have shown that dermoscopy can be a useful tool for the clinical diagnosis of AA by the presence of cadaverized hairs (black dots), exclamation mark hairs (tapering hairs), broken hairs, yellow dots and clustered short vellus hairs in the hair loss areas. 10 Black dots as remnants of exclamation mark hairs or broken hairs provide a sensitive marker for disease activity as well as severity of AA. 10 Yellow dots, are considered to be the most sensitive dermoscopic feature of AA.…”
Section: Introductionmentioning
confidence: 99%